PENETRATION TESTING - Y. Zh. Aitkhozhayeva, Y. Zh.; A. A. Ziro, A. A.; Zhaibergenova, Zh. A.; Baltabay, A. G. (Scientific Journal of Pedagogy and Economics, 2018)
Detection of vulnerabilities is an important composite component of both internal and external audit of information security systems. Potential internal vulnerabilities can be revealed by testing for penetration. At the same time, both the commercial and being in the free access instruments of penetration test are used differently. The review of recognized methodologies (standards) of conducting testing for penetration is made. The list of free distribution kits of instruments of penetration test is provided. One of the widespread attacks is BackDoor allowing to receive control over the attacked system. With the help of the utility of Msfvenom which is a part of a free distribution kit of penetration test Kali Linux with methodology of PTES the attack of BackDoor by implementation of an exploit is successfully realized. Control over the attacked virtual machine was as a result received.